Botulinum Neurotoxins in Cancer Therapy - Bangsumruaj, Janpen (Journal of Health Science of Thailand, 2017)
Botulinum neurotoxins (BoNTs) are produced by Clostridium botulinum, an anaerobic sporeformer gram positive bacillus. BoNT protease disables synaptic vesicle exocytosis by cleaving their cytosolic SNARE (soluble NSF attachment protein receptor) substrates that induce muscle weakness. It has become a valuable method in the treatment of neurological disorders such as cervical dystonia and blepharospasm. It has also been found to be anti-cancer by inhibiting norepinephrine releases for open tumor vessels. BoNT protease provides for tumor oxygenation and perfusion which leads to a substantial improvement in the tumor’s response during radiotherapy or chemotherapy. When directly affecting germinating bacteria, hydrolytic enzymes, such as proteases and lipases, are secreted to destroy cancerous cells. Lastly, it reduces muscle toning by relieving spasms resulting from cancer or therapies. However, the anti-cancer effect of BoNT is not yet fully understood, therefore, further study is required.